Kommunale Bündnisse im Patrimonium Petri des 13. Jahrhunderts - Abel, Christina (Bibliothek des Deutschen Historischen Instituts in Rom, 2019)
In the Middle Ages, Italian communes coordinated their political relations through leagues. The Popes were confronted with this phenomenon as they set up their secular dominion in the 13th century. The study analyzes the terms and texts of the alliances in the Patrimonium Petri, examines their impact on the region, and investigates how the Roman Church dealt with its subjects' autonomous interactions.